2018
DOI: 10.1080/02699052.2018.1429022
|View full text |Cite
|
Sign up to set email alerts
|

Attentional dysfunction and recovery in concussion: effects on the P300m and contingent magnetic variation

Abstract: MEG-evoked responses to the ANT reveal neurophysiological evidence of attentional dysfunction within days of injury. A pattern of improvement was also observed over the course of three months for the P300m, while behavioural performance did not change significantly. Further development of this method may yield a useful adjunct to neurological examination for concussion diagnosis and monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…By utilizing the functional near-infrared spectroscopy (fNIRS) technique, Hibino et al reported significantly increased medial frontal activation and decreased lateral frontal activation in a small sample of young adult patients with severe TBI, as compared to healthy controls, during the performance of an attention task [ 19 ]. During the magnetoencephalography (MEG) recording, Petley et al showed reduced global activation and delayed reaction times when performing a visual attention task in patients with mild TBI compared to controls [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…By utilizing the functional near-infrared spectroscopy (fNIRS) technique, Hibino et al reported significantly increased medial frontal activation and decreased lateral frontal activation in a small sample of young adult patients with severe TBI, as compared to healthy controls, during the performance of an attention task [ 19 ]. During the magnetoencephalography (MEG) recording, Petley et al showed reduced global activation and delayed reaction times when performing a visual attention task in patients with mild TBI compared to controls [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the nine papers that included task-based analyses; three assessed working memory ( Shah-Basak et al, 2018 , Popescu et al, 2019 , Huang et al, 2019cc ), two set-shifting ( da Costa et al, 2015 , Pang et al, 2016 ), and one visual attention ( Petley et al, 2018 ), visual tracking ( Diwakar et al, 2015 ), picture naming ( Popescu et al, 2017 ), and auditory information processing ( Kaltiainen et al, 2019 ). These tasks were performed during the MEG recording, while the analyses above only used resting state data.…”
Section: Resultsmentioning
confidence: 99%
“…The same group showed that connectivity between the occipital lobes and the rest of the brain in the alpha frequency band was reduced in mTBI participants compared to controls ( Pang et al, 2016 ). Petley et al showed reduced global field strength and delayed reaction times in a small sample of mTBI participants compared to controls during a visual attention task ( Petley et al, 2018 ). Visual tracking of an intermittently obscured target showed lower performance in mTBI participants and was associated with widespread relative changes in beta frequency band power compared to controls ( Diwakar et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations